À la folie de Joy Sorman - Julia Pont; Sam Rachebœuf-Allard (Itinéraires)
Joy Sorman's À la folie (2021) is presented as a novel in which the reader follows the narrator's visits to a psychiatric hospital. However, it is more of a field study, part of the non-fictional writings which have flourished in contemporary French literature. This paper aims at demonstrating that this narrative is above all a book of bodies and voices, whose writing attempts to become an echo chamber. The project confronts the difficult question of the restitution and of the right distance to keep with regard to the individuals encountered. If Joy Sorman's approach is tended by the will not to vampire the words and gestures of those she meets, we must wonder about the implications both aesthetic and ethical of its restitution. For À la folie is also the diary of colorful bodies whose representations and the imaginary that they carry can be questioned, whose accuracy can also be questioned. By studying the way in which the author negotiates the gap, the following article intends to show that Joy Sorman's book is precisely an investigation on the edge, torn between paradoxical gestures and representations of which the writing keeps the trace.